2018
DOI: 10.1503/cjs.015417
|View full text |Cite
|
Sign up to set email alerts
|

Can pain catastrophizing be changed in surgical patients? A scoping review

Abstract: Background: Catastrophizing, a coping style characterized by an exaggerated negative affect when experiencing or anticipating pain, is an important factor that adversely affects surgical outcomes. Various interventions have been attempted with the goal of reducing catastrophizing and, by extension, improving treatment outcomes. We performed a systematic review to determine whether catastrophizing can be altered in surgical patients and to present evidence for interventions aimed at reducing catastrophizing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 70 publications
3
38
0
Order By: Relevance
“…The changes in PCS scores following CBT were selected within the range 0 to −19 consistent with of interventions for changing PCS scores in surgical patients. 9 The primary outcome for phase 2 was the difference in the proportion of subjects that achieved a 3-month decrease in WOMAC pain subscale >4. The primary outcome was compared between groups using the proportions test and the relative risk of an increase in the proportion of patients with…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The changes in PCS scores following CBT were selected within the range 0 to −19 consistent with of interventions for changing PCS scores in surgical patients. 9 The primary outcome for phase 2 was the difference in the proportion of subjects that achieved a 3-month decrease in WOMAC pain subscale >4. The primary outcome was compared between groups using the proportions test and the relative risk of an increase in the proportion of patients with…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of studies examining interventions to reduce catastrophizing, Gibson and Sabo found that CBT interventions reduced PCS scores from 0 to −19. 9 The effects were assessed across multiple study types and was not adjusted for confounding variables. They also reported that the mean clinically important reduction in the PCS score was −9.1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients undergoing total knee arthroplasty, the level of pain catastrophizing is associated with higher postoperative pain, lower quality of life and lower patient reported outcomes after surgery [ 4 , 14 , 25 ]. Pain catastrophizing can be modified and is under influence of several factors, such as surgery, physical therapy, cognitive behavioral therapy and pharmacotherapy [ 11 ]. Surgical treatment itself can be a reason for a decrease in pain catastrophizing but it is important to realize that there is a group of patients that might benefit from pre-operative counseling, physiotherapy or even pharmacotherapy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pain catastrophizing can be modified and is under influence of several factors, such as surgery, physical therapy, cognitive behavioral therapy and pharmacotherapy [ 11 ]. Surgical treatment itself can be a reason for a decrease in pain catastrophizing but it is important to realize that there is a group of patients that might benefit from pre-operative counseling, physiotherapy or even pharmacotherapy [ 11 ]. There is literature that shows a significant decrease in pain catastrophizing after a cognitive behavioral therapy program prior to orthopedic surgery [ 7 ].…”
Section: Discussionmentioning
confidence: 99%